Merchants, prices and justice: Pedro de Oñate and Scotus’ labour theory of value: a philosophical approach to the question of economic value - Perpere Viñuales, Álvaro (2022)
Fil: Perpere Viñuales, Alvaro. Pontificia Universidad Católica Argentina; Argentina